Jam Doa “PERMATA” sebagai Pelayanan Kaum Muda Kontemplatif di Gereja Batak Karo Protestan - Louise Febina Sinukaban (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2026)
Generation Z is a digital generation for whom social media plays a significant role in identity formation. This condition requires churches to develop youth ministries that correspond to the spiritual needs and distinctive characteristics of this generation. The Protestant Karo Batak Church (GBKP) responds to this need through Jam Doa PERMATA, or the PERMATA Prayer Hour, a Bible study method that encourages young people to slow down, reflect, and experience the presence of God contemplatively. This study aims to analyze Jam Doa PERMATA as a form of contemplative youth ministry within the context of Generation Z’s digital life. It employs a qualitative method based on observations conducted in a local church, using Mark Yaconelli’s theory of contemplative youth ministry as the analytical framework. The findings indicate that Jam Doa PERMATA provides a space for young people to express their concerns, experience silence, and recognize and interpret the presence of God in their lives. The provision of contemplative space in fellowship and Bible study also demonstrates the church’s involvement in the spiritual formation of Generation Z. Therefore, Jam Doa PERMATA can be further developed as a relevant, contextual, and sustainable model of youth ministry amid the continuing development of the digital world.